Comparative Study of CaMsrB2 Gene Containing Drought‐Tolerant Transgenic Rice (Oryza sativa L.) and Non‐Transgenic Counterpart. (29th August 2014) - Dhungana, S. K.; Kim, B.‐R.; Son, J.‐H.; Kim, H.‐R.; Shin, D.‐H.
Abstract Concerns regarding the safety of transgenic foods have been raised because of possibility of undesirable effects development during genetic engineering. Analysis of phenotypic traits can increase the likelihoods of identifying those unintended effects in dietary composition of the GM crops. Objective of this study was to compare the transgenic lines with their non‐transgenic counterpart. Different vegetative and reproductive traits as well as antioxidant properties were considered to evaluate the transgenic (HV8 and HV23) lines containing CaMsrB2 gene and their non‐transgenic (Ilmi) parent line. Grain size and weight, seed germination, root length, root and shoot dry weight, length and width of flag leaf, plant height, and ligule, stamen and carpel length were not significantly different. Onset and completion of heading in each line occurred almost during the same period. The antioxidant properties in terms of DPPH (1, 1‐diphenyl‐2‐picrylhydrazyl) radical scavenging activity and polyphenol content were not statistically different under same treatment condition. The results suggested that the transgenic rice lines containing CaMsrB2 gene were equivalent to their non‐transgenic counterpart without any visible unintended effects.